Seatbelt‐induced extrathoracic lung herniation. Issue 11 (16th July 2020) - Kitridis, Dimitrios; Karaiskos, Theodoros; Chalidis, Byron; Galanis, Nikiforos; Givissis, Panagiotis
Abstract: Traumatic lung herniation is an uncommon complication of blunt chest trauma due to seatbelt injury. High index of suspicion, adherence to ATLS guidelines, and cooperation between different surgical specialties for the prompt stabilization of flail chest and primary or prosthetic closure of the defect may ensure a favorable outcome. Abstract : Traumatic lung herniation is an uncommon complication of blunt chest trauma due to seatbelt injury. High index of suspicion, adherence to ATLS guidelines, and cooperation between different surgical specialties for the prompt stabilization of flail chest and primary or prosthetic closure of the defect may ensure a favorable outcome.